Endoscopic Vacuum Therapy for Left-Sided Colorectal Anastomotic Leak Without Fecal Diversion. Issue 3 (March 2022) - Kühn, Florian; Hasenhütl, Sandro Michael; Hofmann, Felix O.; Wirth, Ulrich; Drefs, Moritz; Werner, Jens; Schiergens, Tobias S.
Abstract : BACKGROUND: Endoscopic vacuum therapy for the treatment of rectal anastomotic leak has been shown to be effective and safe. The majority of patients are treated after fecal diversion to avoid further septic complications. OBJECTIVE: To report the effectiveness of endoscopic vacuum therapy for rectal anastomotic leak without diversion compared to secondary stoma creation. DESIGN: Retrospective cohort analysis. SETTINGS: University hospital, single-center. PATIENTS: Patients undergoing sigmoid or rectal resection without fecal diversion during primary surgery who were treated with endoscopic vacuum therapy for clinically relevant anastomotic leak. MAIN OUTCOME MEASURES: Treatment success (sepsis control, granulation and closure of the leak cavity, and no subsequent interventional or surgical procedure required); treatment duration; complications associated with endoscopic vacuum therapy; outpatient treatment; and restoration of intestinal continuity in diverted patients. RESULTS: Fifty-seven patients were included. In 20 patients (35%), endoscopic vacuum therapy was initiated without secondary diversion since the leak was extraperitoneal, and the sponge could be placed into the leak cavity with an adequate seal toward the lumen. In 18 patients (90%), this approach was successful. None of these patients required subsequent diversion in the further course of their disease. In two patients, secondary diversion was necessary due to treatment failure. Balloon dilatation for luminal stenosis was required in two patients. When comparing patient and treatment characteristics of patients with and without a stoma, including treatment success and duration, no significant differences were found. Restoration of intestinal continuity was achieved in 69% of diverted patients. LIMITATIONS: Unrandomized, retrospective study design; confounding factors of treatment assignment; low patient numbers and short follow-up of diverted patients; and low statistical power. CONCLUSION: In this single-institution study, endoscopic vacuum therapy for rectal anastomotic leak was successful in 90% of patients without diversion with regard to sepsis control, granulation of the leak cavity, avoidance of surgery, and long-term stoma-free survival. See Video Abstract at http://links.lww.com/DCR/B737 . TERAPIA ENDOSCÓPICA POR ASPIRACIÓN AL VACÍO EN CASOS DE FUGA ANASTOMÓTICA RECTO-CÓLICA IZQUIERDA SIN OSTOMÍA DE PROTECCIÓN ANTECEDENTES: Se ha demostrado que la terapia endoscópica por aspiración al vacío en casos de fuga anastomótica recto-cólica izquierda en el tratamiento de la fuga anastomótica rectal es eficaz y segura. La mayoría de los casos beneficiaron del tratamiento después de la confeción de un ostomía de protección para evitar más complicaciones sépticas. OBJETIVO: Demostrar la efectividad de la terapia endoscópica por aspiración al vacío en casos de fuga anastomótica recto-cólica izquierda sin ostomía de protección comparada con los casos que tuvieron la creación de una ostomía secundaria. DISEÑO: Análisis de cohortes de tipo retrospectivo. AJUSTE: Hospital universitario, unicéntrico. PACIENTES: Aquellos pacientes sometidos a una resección sigmoidea o rectal sin ostomía de protección durante una cirugía primaria, y que fueron tratados con terapia endoscópica por aspiración al vacío en caso de fuga anastomótica clínicamente relevante. PRINCIPALES MEDIDAS DE RESULTADO: Tratamiento exitoso (control de la sepsis, granulación y cierre de la cavidad de la fuga, sin requerir procedimiento quirúrgico o intervención ulteterior); duración del tratamiento; complicaciones asociadas con la terapia endoscópica por aspiración al vacío; tratamiento ambulatorio; restablecimiento de la continuidad intestinal en los pacientes portadores de ostomía. RESULTADOS: Se incluyeron 57 pacientes. En 20 pacientes (35%), se inició la terapia endoscópica por aspiración al vacío sin derivación secundaria, ya que la fuga era extraperitoneal y la esponja podía colocarse en la cavidad de la fuga con un sellado adecuado hacia el lumen. En 18 pacientes (90%), este enfoque fue exitoso. Ninguno de estos pacientes requirió una derivación posterior durante la evolución de la enfermedad. En dos pacientes, fue necesaria una derivación secundaria debido al fracaso del tratamiento. Se requirió dilatación con balón por estenosis luminal en dos pacientes. Al comparar las características de los pacientes y del tratamiento con y sin ostomía, incluido el éxito y la duración del tratamiento, no se encontraron diferencias significativas. El restablecimiento de la continuidad intestinal se logró en el 69% de los pacientes derivados. LIMITACIONES: Diseño de estudio retrospectivo no aleatorio; factores de confusión en la asignación del tratamiento; escaso número de pacientes y seguimiento a corto plazo de los pacientes ostomizados; bajo poder estadístico. CONCLUSIÓN: En este estudio de una sola institución, la terapia al vacío por vía endoscópica en casos de fuga anastomótica rectal fue exitosa en el 90% de los pacientes sin derivación con respecto al control de la sepsis, granulación de la cavidad de la fuga, como se evitó la cirugía y la sobrevida sin ostomía a largo plazo. Consulte Video Resumen en http://links.lww.com/DCR/B737 . ( Traducción—Dr. Xavier Delgadillo )